Real‐world use of adjunctive perampanel for focal‐onset seizures in Italy: A mirroring clinical practice study of perampanel in adults and adolescents (AMPA) - Alfredo D'Aniello; Anna Teresa Giallonardo; Paolo Tinuper; Oriano Mecarelli; Umberto Aguglia; Giovanni Assenza; Antonio Gambardella; Maria Paola Canevini; Renato Scifo; Stefano Meletti; Valentina De Giorgis; Enrica Bonanni; et al. (Epilepsia Open)
Abstract Objective The AMPA study (Study 501; NCT04257604) was a multicenter, prospective, 12‐month observational study in Italy that evaluated the effectiveness and safety of adjunctive perampanel in patients with focal‐onset seizures (FOS), with or without focal to bilateral tonic–clonic seizures (FBTCS). Methods Patients aged ≥12 years with insufficiently controlled FOS, with or without FBTCS, receiving 1–3 anti‐seizure medications (ASMs) were prescribed adjunctive perampanel per the approved indication. The primary endpoint was the median percent change in total seizure frequency per 28 days from baseline at Month 6. Baseline seizure frequency per 28 days was calculated using seizure diaries and/or medical records of seizures occurring in the 8 weeks prior to the baseline visit while patients were receiving 1–3 ASMs. Treatment‐emergent adverse events (TEAEs), including serious TEAEs, were monitored for up to 12 months. Results Of the 240 patients enrolled in the study, 234 were included in the Full and Safety Analysis Sets. Median age (minimum, maximum) was 36.0 years (12, 84) and 51.3% (n = 120/234) were female. The majority of patients (77.8% [n = 182/234]) received ≥2 concomitant ASMs at baseline, with the most common being carbamazepine (33.8% [n = 79/234]). The median percent reduction in total seizure frequency per 28 days from baseline (95% confidence interval) was 55.4% (46.7%–66.7%) at Month 6. Overall, the retention rate was 57.3% (n = 134/234) following 12 months of treatment. During the study, the overall incidence of TEAEs was 56.4% (n = 132/234), with the most frequently reported TEAE being dizziness/vertigo (21.8% [n = 51/234]). Serious TEAEs were experienced by 6.0% (n = 14/234) of patients and no deaths were reported during the 12‐month treatment period. Significance Data from the AMPA study suggest that adjunctive perampanel is associated with improvement in seizure control and with good retention rates and tolerability in a real‐world clinical setting. These findings further support the use of adjunctive perampanel as a suitable treatment option for adolescent and adult patients with epilepsy. Plain Language Summary Our study looked at teenage and adult patients with epilepsy in Italy who took the study drug, called perampanel, as well as the epilepsy treatments they had already been prescribed. After 12 months, 134 out of 234 patients were still using perampanel. Patients taking perampanel had fewer seizures than they did before they started taking perampanel. Side effects occurred in 132 patients (most commonly dizziness/vertigo, irritability, and sleepiness) and caused 45 of them to withdraw from the study. Perampanel was a suitable treatment option for teenage and adult patients with epilepsy.